A Little “Right” Musick: The Unconstitutional Judicial Creation of Private Rights of Action Under Section 10(b) of the Securities Exchange Act - Michael J. Kaufman (Washington University Law Quarterly, 1994)
This Article engages in that reconsideration and offers a constitutional argument for the elimination of the judicially-created private right of action under section 10(b).
Keywords: Securities law; Securities Exchange Act; United States; Implied right of action (Law); Constitutional law